Sastera Untuk Kanak-Kanak: Fungsi dan Implikasinya - Ayob, Salmah (Penerbit Universiti Sains Malaysia, 1981)
This paper portravs Children's Literature as an educational medium to impart moral knowledge and broaden aesthetic perception of life with all its inherent intricacies. It explores the intellectual mechanisms of Children's Literature which present to the children the varied ways of life in different cultures, beliefs, and values which infuse latent influences on the development of their personality. The paper shows that these characteristics are artistically manipulated in the various categories of Children's Literature such as folktales, folklores, fairy tales, legends, comics, biographies, and science fictions.